Perhitungan Rasio Profitabilitas Pada Hj Vera Furniture - Handitia Putra, Jamal; Fauziyah, Hikmah; Sandi, Santi Pertiwi Hari; Hidayaty, Dwi Epty (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The purpose of this visit is to determine the health of Hj Vera Furniture based on financial performance using profitability ratios. The author uses secondary data types. The method in this writing is descriptive quantitative by taking financial data from company data in the form of balance sheets and profit and loss for the 2021 and 2022 periods, then taking theories related to the problem under study. Hj Vera Furniture is a trading company engaged in the furniture industry in the city of Karawang. This business has the goal of producing high-quality assessments that require financial statement analysis to determine company performance. The financial analysis used is to use the calculation of profitability ratios. The results of this writing indicate that the financial condition of Hj Vera Furniture is quite good despite experiencing a decline in percentages in 2021 and 2022. However, the data results for 2021 and 2022 are still above the industry standard average.